Determining the Optimum Portfolio of Sharia Stocks Using an Approach of Shariah Compliant Asset Pricing Model (SCAPM) - Fakhri Husein; Shofia Mauizotun Hasanah (Journal of Economics, Business, and Accountancy Ventura, 2016)
Shariah Compliant Asset Pricing Model (SCAPM) is a modification of the model Capital Asset Pricing Model (CAPM). This research is quantitative descriptive study of theories of optimal portfolio analysis applied to trading stocks, especially in stocks Jakarta Islamic Index. Sampling technique used was purposive sampling and obtained 26 shares. The analysis tool used is MatLab R2010a. The results of this study are not prove theMarkowitz portfolio theory. This is explained by the amount of Beta market (Î²_m) a value beta below 1 indicates that the fluctuation of stocks returns do not follow the movement of market fluctuations. Investors are likely to want a high profit, the investors are advised to choose a second portfolio groups, with rate of 0.176722% and investors are likely to enjoy a substantial risk in the investment portfolio are advised to choose the first group with a great risk of 0.8501%.